INTERACTION OF CHRYSIN AND SOME NOVEL FLAVONES WITH DPPC MODEL MEMBRANE:STUDY BASED ON MD SIMULATION, DSC AND NMR - RAGINI SINHA; URMILA J. JOSHI; SUDHA SRIVASTAVA; GIRJESH GOVIL (International Journal of Pharma and Bio Sciences, 2014)
Modified flavone derivatives show diverse pharmacological effects, which may be attributed to their interaction with lipid membranes. We have studied the interaction of Chrysin (C) and some novel flavone derivatives, 4´–methoxyflavone (C1), 4´–chloroflavone (C2) and 4´–nitroflavone (C3) with dipalmitoylphosphatidylcholine (DPPC) using molecular dynamic (MD) simulation, differential scanning calorimetry (DSC) and multinuclear NMR. MD simulations indicate hydrogen bonding interaction as the most important interaction of chrysin. All the compounds cause an ordering effect on the membranes and their preferential locations depend upon the substituents. DSC studies indicate interactions of these compounds with both polar head group region as well as the alkyl chain region of DPPC. The NMR results of C3 indicate that C3 is located near sn–3–glycero carbon. C and C1 are inserted deeper while C2 interacts with polar headgroups. C3 shows significant antiproliferative activity.